Pupils' parents', and teachers' perception of homework as related to certain variables - Ang, Gerarda Pangilinan 1946- (s.n.], 1970)
The purpose of the study is to determine and compare the perceptions of grades V and VI pupils and those of the parents and the teachers regarding homework assigned to the students as it is related to their home life, social activities, and academic achievement